Swimbladder Function in the European Eel Anguilla anguilla - Bernd Pelster (Fishes, 2023)
Eels use the swimbladder for buoyancy control. The ductus pneumaticus connecting the esophagus with the swimbladder is closed soon after initial opening of the swimbladder in the glass eel stage, so that eels are functionally physoclist. Subsequent filling of the swimbladder is achieved by activity of gas gland cells in the swimbladder epithelium and countercurrent concentration in the rete mirabile. Gas gland cells produce and release lactic acid and CO2. In blood, acidification induces a release of oxygen from the hemoglobin (Root effect). The resulting increases in PO2 and PCO2 provide diffusion gradients for the diffusion of oxygen and CO2 into the swimbladder, the main gases secreted into the swimbladder. In addition, the partial pressure of these two gases remains elevated in venous blood leaving the swimbladder epithelium and returning to the rete mirabile. Back-diffusion from venous to arterial capillaries in the rete results in countercurrent concentration, allowing for the generation of high gas partial pressures, required for filling the swimbladder under elevated hydrostatic pressure. The transition of the yellow eel to the silver eel stage (silvering) is accompanied by a significant improvement in swimbladder function, but swimbladder volume cannot be kept constant during the daily vertical migrations silver eels perform during their spawning migration back to the spawning grounds in the Sargasso Sea. Infection of the swimbladder with the nematode Anguillicola crassus significantly impairs the function of the swimbladder as a buoyancy organ.